A law of her own : the reasonable woman as a measure of man - Forell, Caroline A. (Book collections on Project MUSE., 2000)
"In A Law of Her Own, the authors propose to radically change law's fundamental paradigm by introducing a "reasonable woman standard" for measuring certain behavior. Advocating that courts apply this standard to the conduct of men - and women - in legal settings where women are overwhelmingly the injured parties, the authors seek to eliminate the victimization and objectification of women by dismantling part of the legal structure that supports their subordination."--Jacket